Specific Role for GSK3α in Limiting Long-Term Potentiation in CA1 Pyramidal Neurons of Adult Mouse Hippocampus - Ebrahim Amini, Aeen; Miyata, Tsukiko; Lei, Gang; Jin, Fuzi; Rubie, Elizabeth; Bradley, Clarrisa A.; Woodgett, James R.; Collingridge, Graham L.; Georgiou, John (Frontiers in Molecular Neuroscience, 2022)
Glycogen synthase kinase-3 (GSK3) mediates phosphorylation of several hundred proteins, and its aberrant activity is associated with an array of prevalent disorders. The two paralogs, GSK3α and GSK3β, are expressed ubiquitously and fulfill common as well as unique tasks throughout the body. In the CNS, it is established that GSK3 is involved in synaptic plasticity. However, the relative roles of GSK3 paralogs in synaptic plasticity remains controversial. Here, we used hippocampal slices obtained from adult mice to determine the role of each paralog in CA3−CA1 long-term potentiation (LTP) of synaptic transmission, a form of plasticity critically required in learning and memory. Conditional Camk2a Cre-driven neuronal deletion of the Gsk3a gene, but not Gsk3b, resulted in enhanced LTP. There were no changes in basal synaptic function in either of the paralog-specific knockouts, including several measures of presynaptic function. Therefore, GSK3α has a specific role in serving to limit LTP in adult CA1, a postsynaptic function that is not compensated by GSK3β.